Evaluation of the patadyong weaving industry under the Bagtason Loom Weavers Association (BLWA) in barangay Bagtason, Bugasong, Antique - Calibjo, Zygred Mariano
ABSTRACT This case study was conducted to evaluate the patadyong weaving industry (PWI) in Barangay Bagtason, Bugasong Antique. Purposive sampling method was used in selecting respondents composed of eight center-based weavers; three patadyong sellers; one representative from each local government units (LGUs), specifically, the Department of Trade and Industry (DTI), Antique's Department of Tourism, and Antique Provincial Planning Development (PPDO), and one representative from a non-government organizations (NGOs) - the Antique Development Foundation (ADF). The interview and observation guide served as instruments for gathering primary data. Results showed that the current patadyong weaving industry is headed by BLWA. BLWA's members are all weavers in Barangay Bagtason. The production of patadyong is handled by the association and the finished patadyong is distributed to direct customers or for consignment. For the industry's marketing and accounting, the BLWA get assistance from ADF. The researcher concluded that the patadyong weaving industry has no observable growth because their primary goal is not to grow but to have a sustainable industry. In fact, the mission and vision of the BLWA aims to promote and develop its internal system. It simply aims to develop and promote the welfare of its members/weavers, the community, and the organization. To maximize the potential of the industry, further trainings for weavers and interested youth and activities to boost cultural tourism in Barangay Bagtason are recommended for the sustainability of the industry.